Effect of Saline Water on Germination and Growth of Ziziphus Species - Dass, H C; Jain, B L (Annals of Arid Zone, 2016)
Ziziphus rotundifolia Lomk .Z. mauritiana Lamk cv Tikadi, Z. numularia (Burm. f.) Wight & Am. and Z. spinachristi (L.) Willd. were screened for tolerance to saline irrigation water (EC 0.5 to 65 mmhos) at germination and seedling growth stages. Z. rotnndifolia, commonly used as rootstock for ber, was tolerant to i. rigation water salinity upto 4.5 and 6.5 mmhos EC at germination and seedling growth stages. respectively. Ziziphus spinachisti and Z. mauritiana cv Tikadi were moderately tolerant upto 2.5 mmhos EC, Z, hummularia was sensitive to salinity.